Electron Flow From the Inner Membrane Towards the Cell Exterior in Geobacter sulfurreducens: Biochemical Characterization of Cytochrome CbcL - Antunes, Jorge M. A.; Silva, Marta A.; Salgueiro, Carlos A.; Morgado, Leonor (Frontiers in Microbiology, 2022)
Exoelectrogenic microorganisms are in the spotlight due to their unique respiratory mechanisms and potential applications in distinct biotechnological fields, including bioremediation, bioenergy production and microbial electrosynthesis. These applications rely on the capability of these microorganisms to perform extracellular electron transfer, a mechanism that allows the bacteria to transfer electrons to the cell´s exterior by establishing functional interfaces between different multiheme cytochromes at the inner membrane, periplasmic space, and outer membrane. The multiheme cytochrome CbcL from Geobacter sulfurreducens is associated to the inner membrane and plays an essential role in the transfer of electrons to final electron acceptors with a low redox potential, as Fe(III) oxides and electrodes poised at -100 mV. CbcL has a transmembranar di-heme b-type cytochrome domain with six helices, linked to a periplasmic cytochrome domain with nine c-type heme groups. The complementary usage of ultraviolet-visible, circular dichroism and nuclear magnetic resonance permitted the structural and functional characterization of the CbcL periplasmic domain. The protein was found to have a high percentage of disordered regions and its nine hemes are low-spin and all coordinated by two histidine residues. The apparent midpoint reduction potential of the CbcL periplasmic domain was determined, suggesting a thermodynamically favorable transfer of electrons to the putative redox partner in the periplasm  the triheme cytochrome PpcA. The establishment of a redox complex between the two proteins was confirmed by probing the electron transfer reaction and the molecular interactions between CbcL and PpcA. The results obtained show for the first time how electrons are injected into the periplasm of Geobacter sulfurreducens for subsequent transfer to the cell’s exterior.